2012
DOI: 10.1007/s10040-011-0816-0
|View full text |Cite
|
Sign up to set email alerts
|

Political economy of the energy-groundwater nexus in India: exploring issues and assessing policy options

Abstract: Groundwater is now a major source of agricultural water supply in many parts of the world. The value of groundwater as a new source of supply is well known. However, its additional buffering or stabilization value is less appreciated and even less analysed. Knowledge on groundwater's stabilization value is advanced by developing and estimating an empirical model using the case of tank irrigation systems in Tamil Nadu, India. Unlike previous work, the model uses cross-sectional rather than time-series data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 7 publications
0
63
0
1
Order By: Relevance
“…Previous studies have shown the complex interaction of groundwater depletion and energy subsidies in India, since groundwater extraction relies heavily on electric pumping and free electricity for farmers [16]. In northwestern India, agricultural pumping leads to the long-term fall of water tables in deep alluvial aquifers [6][7][8], but the annual groundwater abstraction rate seems to be constrained by shortages of energy rather than groundwater [40].…”
Section: The Indian Agriculture Groundwater and Energy Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the complex interaction of groundwater depletion and energy subsidies in India, since groundwater extraction relies heavily on electric pumping and free electricity for farmers [16]. In northwestern India, agricultural pumping leads to the long-term fall of water tables in deep alluvial aquifers [6][7][8], but the annual groundwater abstraction rate seems to be constrained by shortages of energy rather than groundwater [40].…”
Section: The Indian Agriculture Groundwater and Energy Nexusmentioning
confidence: 99%
“…This financial support changed the status of this water resource from an emergency supply, in case of surface water scarcity, to the main water source for irrigated crops [16]. To cope with the recurrent groundwater shortages associated with deficient monsoon rainfalls and overexploitation, farmers modulate their consumption by limiting the extent of irrigated areas.…”
Section: Introductionmentioning
confidence: 99%
“…And the scale of resource exploitation has accelerated in the last two decades. The number of tubewells was less than a million in 1980, jumped to 8 million in the mid-1990s, and exceeded 15 million by 2010 (Shah et al 2012). In addition to cheaper pumps and low well installation costs, electric power subsidies to farms have played a pivotal role in the phenomenal growth of tubewells and overexploitation of groundwater in 16 major states of India.…”
Section: Northwestern Indiamentioning
confidence: 99%
“…In addition to cheaper pumps and low well installation costs, electric power subsidies to farms have played a pivotal role in the phenomenal growth of tubewells and overexploitation of groundwater in 16 major states of India. The flat power tariff reduced the marginal cost of pumping groundwater to near zero (Shah et al 2012).…”
Section: Northwestern Indiamentioning
confidence: 99%
See 1 more Smart Citation